An Investigation on Using Passive Cooling Roofs Techniques for Improving Climatic Performance of Residential Buildings in Hot Arid Regions based on Post-Occupancy Evaluation of Inhabitants’ Thermal Comfort Appreciations - Wafa, Athmani; Sriti, Leila; Dabaieh, Marwa; Khadraoui, Mohamed Amine (Technium Social Sciences Journal, 2022)
In hot dry climates, employing passive cooling roofs systems can provide cooling needs with less amount of electrical energy. Furthermore, when focusing on living spaces in terms of indoor thermal comfort and energy performance issues, occupant’s interaction with the building should not be underestimated. Recent studies with occupant-based focus have shown that human behaviour significantly impacts energy consumption, even more than building design. Likewise, understanding occupant’s interactions within buildings plays a key role in enhancing the indoor environment performance. To examine the potential for cooling load reduction and thermal comfort enhancement by using cool roofs in residential buildings, a study was performed. Considering a sample of twelve multi-story houses located in the city of Biskra (southern Algeria), thermal comfort conditions were analysed on the basis of a post-occupancy evaluation (POE) survey and in situ recorded measurements campaign. The POE household survey indicated that out of 43 respondents, 54% perceive indoor thermal conditions as “hot” during summer period, while 79.33% of them operate HVAC device day and night. Using interviews, the study also explores social acceptability toward implementing passive roofing techniques. Results showed that cool roof and cool tiles were the best accepted systems with 100% and 90% voted strongly agree. Furthermore, the potential of thermal comfort and energy-efficiency improvements due to cool roofs was investigated through a dynamic simulation using TRNSYS software. Results indicated that air temperature was reduced by an average of 4.11°C to 3.28°C, and cooling loads have decreased to 508.60kWh/m² and 384.54kWh/m² respectively during the hottest period of summer. Therefore, user-centric satisfaction as a research method would enhance future buildings design.